Correlation Between Gender and Students’ Biology Learning Outcomes - Ami, Mucharommah Sartika; Rusdiana, Siti (APPLICATION: Applied science in Learning Research, 2023)
Gender is still an issue that is always linked to students’ ability, including their learning outcomes. This research aims to examine the correlation between gender and students’ biology learning outcomes. The research involved 15 male and 15 female students from classes X, XI, and XII Science at MA Ghozaliyah in the 2022/2023 academic year. Students’ biology learning outcomes were obtained from odd semester final exam scores. Data analysis was carried out statistically using the Eta correlation formula. The research results show that there is a weak negative linear relationship between gender and students’ biology learning outcomes, because the eta value obtained was 2,94 and Fcount < Ftable at a significance level of 0,01.